Sampling the progression of domain-initial denasalization in Seoul Korean. Issue 1 (2nd December 2020) - Yoo, Kayeon; Nolan, Francis
Word-initial nasals in Korean are known to exhibit prosody-sensitive denasalization. The literature on the subject is still scarce and even the basic description of the process is debated. This study tested the speculation that inconsistencies in the literature may be explained if certain features of denasalization have developed relatively recently as part of an ongoing sound change. Based on apparent-time data from thirty-two speakers of Seoul Korean, the study explored the development of denasalization over a fifty-year period. The phonetic manifestations of domain-initial nasals were examined, along with the effects of prosodic position, place of articulation, and the height of the following vowel. The results revealed that denasalization has advanced rapidly over time, acquiring more plosive-like features of devoicing as well as a complete lack of nasality. Alveolar nasals before a high vowel were most likely to show denasalization and devoicing. Interestingly, the cumulative effect of prosody became weakest and partial denasalization was least likely for the younger group. Based on these results, we speculate that Korean denasalization is in the process of being stabilized into a discrete phrase-level process from a more general, gradient phenomenon of domain-initial strengthening, consistent with the theory of the life cycle of phonological processes.